The relationship of apolipoprotein B and very low density lipoprotein triglyceride with hyperuricemia and gout - Rasheed, Humaira (Arthritis Res Ther, 2014)
INTRODUCTION: Gout results from an innate immune response to monosodium urate (MSU) crystals deposited in joints. Increased very low-density lipoprotein (VLDL) has been associated with gout. The apolipoprotein B (apo B), which is present on VLDL, regulates neutrophil response to MSU crystals and has been positively associated with gout. Furthermore, the gene (A1CF) encoding the complementation factor for the APOB mRNA-editing enzyme is associated with urate levels. However, the relationship of apo B and VLDL with gout and hyperuricaemia (HU) is still unclear. Therefore, we tested the association of VLDL and apo B with HU and with gout compared to HU. METHODS: New Zealand European (n = 90) and Māori and Pacific Island (Polynesian) (n = 90) male gout case and control sample sets were divided into normouricaemia (NU), asymptomatic HU and gout groups. Size exclusion chromatography and enzyme-linked immunosorbant assay was used to measure VLDL and apo B. Multivariate logistic regression was used to assess the risk of gout and HU per unit change in VLDL and apo B. RESULTS: Increased levels of VLDL triglycerides (Tg) were observed in the gout sample set compared to NU and HU in Europeans (P = 1.8 × 10(-6) and 1 × 10(-3), respectively), but only compared to NU in Polynesians (P = 0.023). This increase was driven by increased number of VLDL particles in the European participants and by the Tg-enrichment of existing VLDL particles in the Polynesian participants. Each mmol/L increase in VLDL Tg was significantly associated with gout in the presence of HU in Europeans, with a similar trend in Polynesians (OR = 7.61, P = 0.011 and 2.84, P = 0.069, respectively). Each μmol/L increase in total apo B trended towards decreased risk of HU (OR = 0.47; P = 0.062) and, conversely, with increased risk of gout compared to HU (OR = 5.60; P = 0.004). CONCLUSIONS: Increased VLDL Tg is associated with the risk of gout compared to HU. A genetic approach should be taken to investigate the possibility for causality of VLDL in gout. Apolipoprotein B may have pleiotropic effects in determining HU and gout.